2023
DOI: 10.1021/acs.energyfuels.2c03699
|View full text |Cite
|
Sign up to set email alerts
|

Green Leaching of Lithium-Ion Battery Cathodes by Ascorbic Acid Modified Guanidine-Based Deep Eutectic Solvents

Abstract: The replacement of traditional solvents in lithium-ion battery recovery process by deep eutectic solvents (DESs) has been widely reported. This work proposed a DES modified by reducing agents for the efficient leaching of LiCoO2 (LCO) and lithium nickel cobalt manganese oxides (NCMs) to overcome the intractable difficulty of previous research (high viscosity, poor reuse performance, and operation conditions). The DES of guanidine hydrochloride (GUC) and lactic acid (LAC) with 1 wt % ascorbic acid could dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…It is a truism that the viscosity of DESs is mainly given van der Waals force, hydrogen bonding, and electrostatic interactions; the lower viscosity is more favorable to accelerate the liquid–solid reaction and the subsequent separation. , The kinematic viscosities of UC13-FA-DESs with different FA ratios measured at 20–140 °C are shown in Figure e (Table S2). Higher temperature leads to lower viscosity, even from 23.08 to 2.09 cP for the UC13-FA2.4-DESs.…”
Section: Resultsmentioning
confidence: 99%
“…It is a truism that the viscosity of DESs is mainly given van der Waals force, hydrogen bonding, and electrostatic interactions; the lower viscosity is more favorable to accelerate the liquid–solid reaction and the subsequent separation. , The kinematic viscosities of UC13-FA-DESs with different FA ratios measured at 20–140 °C are shown in Figure e (Table S2). Higher temperature leads to lower viscosity, even from 23.08 to 2.09 cP for the UC13-FA2.4-DESs.…”
Section: Resultsmentioning
confidence: 99%
“…This boost was attributed to the stronger acidity of MAL–PSA combination, leading to increased solubility of LIBs in ternary DESs compared with binary DESs. Recently Yan et al 55 reported that GUC based DES exhibited higher acidity compared with DES based on ChCl, and that LA is more acidic than GA when used as HBD for both types of DES. Amongst the four DESs, Li and Co leaching efficiencies increased with increasing acidity.…”
Section: Application Of Dess In Libs Recyclingmentioning
confidence: 99%
“…half that the 1ChCl-1OA leaching of 7 vs. 14.2%. 112 For DESs with HBDs other than oxalic acid including, ChCl-2urea, 40 2ChCl-LA, 114 ChCl-LA, 50 and GUC-LA-VC, 55 oxalic acid is reportedly also used as a stripping reagent to separate transition metals from Li following leaching. The first step was coprecipitation of all transition metals or precipitation of individual metal by OA, followed by precipitation of Li + as Li 2 CO 3 39 or LiPO at Z11 (solvent extraction), and; then back to acidic pH 1.5 (stripping).…”
Section: Metal Recovery and Des Reusementioning
confidence: 99%
“…Several deep eutectic solvents were tested as leaching agents in the presence of different types of additives (i.e., guanidine hydrochloride with ascorbic acid, phytic acid, etc. ). , The optimization of cobalt recovery was carried out by investigating various operating conditions such as reaction time, temperature, solid (black mass) to liquid (DES) ratio, additive type, and concentration. Leaching with the final selected DES ChCl (33%), lactic acid (53%), and citric acid (13%) at 55 °C achieved an extraction yield of more than 95% for cobalt.…”
Section: Battery Disposalmentioning
confidence: 99%